Singing for health: Do members of a generic singing for health group experience similar effects on health and well-being as those in condition-specific groups?. (1st November 2018) - Price, Sonia; Whitfield, Laura
Throughout time, and within differing cultures, music has been understood to have a beneficial impact on health. Group singing, in particular, may have specific benefits for health compared to alternative forms of music making and listening, and there exists a growing body of research examining the impact of singing on health. This mixed-methods study explored the benefits to health and well-being reported by people attending a generic singing for health group. A comparison of findings was made against existing data on the benefits reported by people attending condition-specific groups. Results indicated a similarity in reported benefits and a preference for a generic group, which may have implications for the future commissioning of singing for health groups.